Association of Medicare and Medicaid Insurance Status with Increased Spine Surgery Utilization Rates. Issue 17 (1st September 2021) - Benton, Joshua A.; Weiss, Brandon T.; Mowrey, Wenzhu B.; Yassari, Neeky; Wang, Benjamin; Ramos, Rafael De La Garza; Gelfand, Yaroslav; Castro-Rivas, Erida; Puthenpura, Vidya; Yassari, Reza; Yanamadala, Vijay
Abstract : Study Design: Retrospective single-institution study. Objective: The aim of this study was to determine the relationship between patients' insurance status and the likelihood for them to be recommended various spine interventions upon evaluation in our neurosurgical clinics. Summary of Background Data: Socioeconomically disadvantaged populations have worse outcomes after spine surgery. No studies have looked at the differential rates of recommendation for surgery for patients presenting to spine surgeons based on socioeconomic status. Methods: We studied patients initially seeking spine care from spine-fellowship trained neurosurgeons at our institution from July 1, 2018 to June 30, 2019. Multivariable logistic regression was used to assess the association between insurance status and the recommended patient treatment. Results: Overall, 663 consecutive outpatients met inclusion criteria. Univariate analysis revealed a statistically significant association between insurance status and treatment recommendations for surgery ( P  < 0.001). Multivariate logistic regression demonstrated that compared with private insurance, Medicare (odds ratio [OR] 3.54, 95% confidence interval [CI] 1.21–7.53, P  = 0.001) and Medicaid patients (OR 2.46, 95% CI 1.21–5.17, P  = 0.014) were more likely to be recommended for surgery. Uninsured patients did not receive recommendations for surgery at significantly different rates than patients with private insurance. Conclusion: Medicare and Medicaid patients are more likely to be recommended for spine surgery when initially seeking spine care from a neurosurgeon. These findings may stem from a number of factors, including differential severity of the patient's condition at presentation, disparities in access to care, and differences in shared decision making between surgeons and patients. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textWe analyze the association between insurance status and treatment recommendations for outpatients seen at a single institution's neurosurgical spine clinics. Surgery recommendation rates differed among insurance groups. Studying these disparities will provide better insights into the significant differences in surgical outcomes seen in socioeconomically disadvantaged populations.